Revealing the Underlying Mechanism of Diabetic Nephropathy Viewed by Microarray Analysis - Qu, W.; Han, C.; Li, M.; Zhang, J.; Li, L. (Experimental and Clinical Endocrinology & Diabetes, 2015)
To explore the molecular mechanisms of diabetic nephropathy (DN) progression and provide the theoretical basis for treating DN, GSE1009 microarray data were downloaded from Gene Expression Omnibus database. Microarray data were obtained from glomeruli isolated from normal kidneys (n=3) and kidneys from patients with DN (n=3). We first screened the differentially expressed genes (DEGs) in kidneys by the Linear Models for Microarray Data package in R. Then the function of DEGs in DN was explored through Gene Ontology (GO) and KEGG pathway enrichment analyses. Critical DEGs for DN progression were investigated by constructing PPI network and mining significant modules. Afterwards, enriched protein domains of modules were analyzed by Interpro and DAVID. At last, the regulatory miRNAs for DEGs were calculated by WebGestalt, and DEGs-miRNAs network was visualized with Cytoscape. A total of 666 DEGs including 384 up- and 282 down-regulated genes were screened out. The up-regulated DEGs were significantly enriched in plasma membrane and signal transmission, and mainly participated in pathways of cytokine-cytokine receptor and neuroactive ligand-receptor interaction. The down-regulated DEGs significantly enriched in extracellular region and cytoskeletal protein binding, and mainly participated in ECM-receptor interaction and dilated cardiomyopathy. 2 PPI networks were constructed with confidence score>0.4. One significant module obtained from PPI network for up-regulated DEGs mainly enriched in protein domain of rhodopsin-like G protein-coupled receptors. The down-regulated DEGs were mainly regulated by 10 miRNAs clusters. Together, we constructed a comprehensive molecular network for DN progression and miR-1 and miR-25 might be theoretical targets for DN.
Keywords: diabetic nephropathy; differentially expressed genes; miRNAs; target genes